Instability, economic stagnation and the role of islam in the North Caucasus - Constanze Dobler (Universität Hohenheim, 2011)
Since the breakup of the Soviet Union, the North Caucasus is known as a politically unstable region and as a melting pot for terrorism and all kinds of criminal activity, reaching from drugtrafficking and illegal arms trade to hijacking and extortion. Furthermore, the North Caucasus is one of Russia's poorest and least developed regions. Although the role of Islam as a destabilizing factor should not be overestimated, it is a determining characteristic regarding the region's past and current development. The paper considers specific influencing factors like the North Caucasus' geographical location, foreign influence, its Soviet past, its history of Islamization, its societal structure, its ethnic heterogeneity and the prevalent Russian institutional vacuum with a focus on Islam and its local characteristics. Then it is questioned whether sustainable socio-economic development is possible within the prevalent institutional environment and whether Islam plays a decisive role or not. It is discovered, that weak governance on the central and regional levels and the inability to implement and enforce the rule of law are responsible for the region's socio-economic situation. The form of societal organization plays a role, too. These factors, however, are historically determined and will therefore persist, in part even in the long run.
Keywords: N44; N93; N94; O52; P20; P30; Z12; 330; country studies; economic history; economic systems; formerly centrally planned economies; regional history; religion; Übergangswirtschaft; Islam; Politische Stabilität; Stagnation; Wirtschaftsgeschichte; Pfadabhängigkeit; Kaukasus (Nord)